Nuclear and Radiochemistry - Kónya, József Nagy, Noémi M. (Elsevier insights., 2012)
Explains the basic principles and applications of the primary areas of nuclear and radiochemistry. This title includes nuclear medicine and chemical aspects of nuclear power plants, namely the problems of nuclear wastes and nuclear analysis (both bulk and surface analysis), with analytical methods based on interactions of radiation with matter.